2006
DOI: 10.1200/jco.2005.04.2465
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the Jaw in Multiple Myeloma Patients: Clinical Features and Risk Factors

Abstract: ONJ appears to be time-dependent with higher risk after long-term use of bisphosphonates in older MM patients often after dental extractions. No satisfactory therapy is currently available. Trials addressing the benefits/risks of continuing bisphosphonate therapy are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
384
1
46

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(460 citation statements)
references
References 37 publications
14
384
1
46
Order By: Relevance
“…In another retrospective study of 90 MM patients, ONJ was reported in 3% of patients. 12 Bamias et al 11 reviewed 252 patients with cancer, including 100 with MM, who received at least six infusions of bisphosphonate and reported that the incidence of ONJ was 9.9% among the MM patients. None of the patients treated with pamidronate alone experienced this complication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another retrospective study of 90 MM patients, ONJ was reported in 3% of patients. 12 Bamias et al 11 reviewed 252 patients with cancer, including 100 with MM, who received at least six infusions of bisphosphonate and reported that the incidence of ONJ was 9.9% among the MM patients. None of the patients treated with pamidronate alone experienced this complication.…”
Section: Discussionmentioning
confidence: 99%
“…8 More recently, avascular osteonecrosis of the jaw (ONJ) has been increasingly reported in patients treated with bisphosphonates. [9][10][11][12] This complication usually presents as a non-healing lesion in the oral cavity strictly related to dental procedures. The etiology is still unclear: microcirculatory alterations, a hypercoagulable state or osteomyelitis have been postulated as possible causes.…”
Section: Introductionmentioning
confidence: 99%
“…13 The potential difficulties in creat ing larger problem through injudicious 14 One report has also suggested an increased risk where patients have received two different parenteral preparations sequentially. 15 Although oral bisphosphonates are the most commonly prescribed form of these drugs, the incidence of BON associated with their use represent only approxi mately 11% of reported cases of BON. 16 An expert panel from the American Dental Association 17 has estimated that the risk associated with oral bisphospho nates is in the order of 0.7 per 100,000 prescribed patient years, based on data reported by pharmaceutical companies.…”
Section: Verifiable Cpd Papermentioning
confidence: 99%
“…56 ONJ appears to be time dependent, correlates with type of bisphosphonate, older age and dental extractions. [57][58][59] No satisfactory therapy is currently available, while surgical therapy may help only a subset of myeloma patients with ONJ. 60 Therefore, patients who receive bisphosphonates should improve their oral hygiene, while oncologists and dentists should be aware of this complication and its management.…”
Section: Osteonecrosis Of the Jaw And Bisphosphonatesmentioning
confidence: 99%